2018
DOI: 10.1080/09542299.2018.1531727
|View full text |Cite
|
Sign up to set email alerts
|

Co-transport of Pb (II) and Cd (II) in saturated porous media: effects of colloids, flow rate and grain size

Abstract: The transport of Pb(II) or Cd(II) in subsurface has been studied in the literature; however; their co-transport in porous media in presence of colloids has not been clearly understood. In this work, a series of column experiments were conducted to study Pb(II) and Cd(II) co-transport in saturated porous media under various experimental conditions with different combination of colloidal solution (montmorillonite colloid, manual loessial soil colloid and humic acid), flow rate (0.1, 0.5 and 1.0 ml min −1 ) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Contaminant transport in soil occurs not only in dissolved form but also in association with moving colloids. This mechanism of contaminant migration has been reported for numerous contaminants in the literature, including heavy metals [22,140,141], pesticides [142,143], and pharmaceuticals [33,144,145]. Colloid-associated contaminants may migrate at a rate faster than the non-sorbing tracer [146], which contributes an essential pathway for rapid contaminant transport, especially for highly sorbing organic contaminants in natural soil and groundwater [22,34,[147][148][149].…”
Section: Colloid-facilitated Contaminant Transport Modelsmentioning
confidence: 77%
“…Contaminant transport in soil occurs not only in dissolved form but also in association with moving colloids. This mechanism of contaminant migration has been reported for numerous contaminants in the literature, including heavy metals [22,140,141], pesticides [142,143], and pharmaceuticals [33,144,145]. Colloid-associated contaminants may migrate at a rate faster than the non-sorbing tracer [146], which contributes an essential pathway for rapid contaminant transport, especially for highly sorbing organic contaminants in natural soil and groundwater [22,34,[147][148][149].…”
Section: Colloid-facilitated Contaminant Transport Modelsmentioning
confidence: 77%
“…Consequently, to understand the risk of Cu in groundwater, it is important to study how mineral colloids and HA influence the transport of Cu. It was found that mineral colloids such as HA can promote the migration of adsorbed heavy metals in groundwater, which acts as mobile media, 9 through carboxyl, phenol, and other groups present in HA that promotes the transportation of heavy metals in groundwater 10–12 . Many researches show that there is correlation among heavy metals, colloids, and HA 13–16 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that mineral colloids such as HA can promote the migration of adsorbed heavy metals in groundwater, which acts as mobile media, 9 through carboxyl, phenol, and other groups present in HA that promotes the transportation of heavy metals in groundwater. [10][11][12] Many researches show that there is correlation among heavy metals, colloids, and HA. [13][14][15][16] However, far too little attention has been paid to the interrelations among Cu, colloids, and HA in groundwater, including co-transport and release.…”
mentioning
confidence: 99%
“…The retention and accumulation of NZVI onto different types of soils thus have attracted much research interest [16][17][18][19]. A large number of literature has reported that the adsorbed NZVI particles can be coalesced in soils and gradually lose their activities [20][21][22][23]. In addition, there are also a few studies reporting the release of NZVI particles from sludge [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%